Increasing Public Loyalty through Trust in The Police: The Case Of The Police In Indonesia - Zulganef, Zulganef -; Pratminingsih, Sri Astuti; Purwaningdyah, Sri Wiludjeng Sunu (Jurnal Manajemen Pelayanan Publik, 2024)
This study verifies the role of trust in generating loyalty among the public towards the Republic of Indonesia Police (POLRI). The basis for this verification is related to the gap between POLRI's objectives according to its 2020-2024 strategy and existing facts regarding trust, along with the discrepancy between studies by several researchers and the findings of Zulganef (2006) regarding trust and loyalty. Verification was carried out through a research model adopted from previous research by Zulganef (2022). The method used was a survey using self-administered questionnaires that were distributed to members of the Indonesian public and which yielded responses from 198 people. The results of this research show that loyalty is influenced by trust, while trust is influenced by satisfaction with police behavior and satisfaction with the programs implemented by the police. Meanwhile, another variable, namely the sense of security, does not influence trust, therefore trust not mediates realtionships between sense security and loyalty  towards the police. The authors also provide recommendations to POLRI based on this research.